The modality of Distance Education (de): as a teaching strategy for students with reduced mobility - Frazão, Marjonhy da Silva (Faculdade de Filosofia e Ciências, 2020)
The present study aims to analyze the Distance Education modality (DE) as a strategy in teaching for students with reduced mobility. It is a research of bibliographic review, exploratory and of qualitative character. The research was based on references of books, articles, monographs, dissertations and theses consulted on web sites. People with disabilities generally do not attend public places because of lack of accessibility, while students enrolled in well-designed schools have, on average, significantly better incomes than their peers enrolled in poorly designed schools. It is understood that technology is an important ally of teachers to guarantee the autonomy of students, either to soften barriers or to personalize learning, DL is an important tool with potential for teaching and learning, as well as a motivating and innovative resource for teachers with students with special educational needs (SEN). Thus, the challenge of the school and the teacher is to develop pedagogical practices that enable the improvement of the inclusive process of students with reduced mobility, which is still a subject that requires more scientific research and the expansion of literature in the area.